Reflecting on 2025 and looking towards the next 40 years of AJET - Corrin, Linda; Han, Feifei; Deneen, Chris; Huijser, Henk (Australasian Journal of Educational Technology, 2025)
As the Australasian Journal of Educational Technology’s (AJET) 40th anniversary year draws to a close, we look back over the year to consider what we have learnt from our journey through the past 40 years of AJET articles. We also explore the bibliometric data for 2025 where we see that AJET has experienced the highest number of submissions in its 40-year history. Impact is an important goal for AJET and this year we have seen an increase in our metrics across the various ranking systems that show that AJET is a leading venue for educational technology research and practice as a Q1 journal. We end with a look towards the future for what is to come in 2026 and beyond. Overall, this year has taught us the value of learning from our history, keeping learning at the centre of our research and practice, and the value of community in fostering innovation and quality. We look forward to the next 40 years of AJET’s journey with great interest and enthusiasm as we take inspiration from the past and continue in our quest to provide access to quality educational technology research and practice into the future.